Ethics and Technological Innovation in the Green Transformational Leadership - Saca-Aquino, Ishair (2024)
Green transformational leadership emerges as a fundamental approach to driving sustainability and environmental performance in organisations. It goes beyond traditional management, seeking to inspire and motivate employees towards a shared strategy, policy, culture and vision of ecological responsibility and sustainable development. Given its relevance and the lack of a systematisation of the literature on transformational green leadership with ethics and technological innovation, it was decided to pose two research questions related to these points. In order to answer these questions, a literature review was carried out to identify what has been written on the subject and what the latest trends are. The most significant findings regarding ethics have been reviewed at the level of behaviours, practices and impacts. LWGs possess behaviours, values and attitudes that foster environmental improvement, shape the organisation's strategic orientation, vision, define the organisation's culture and policies. Current practices that relate to GTL have been presented in this research. Also, the generated impacts that are generated show the efforts achieved. In terms of technological innovation, GTLs empower people, inspire them and stimulate their creativity to become agents of technological innovation. This improves not only the performance of the organisation, but also of its employees and other stakeholders, as well as developing environmentally friendly products. This research is relevant and provides significant findings on these issues, which have not been systematised and studied in depth.